The Investment Protection System in Peru - Ferrero Díaz, Javier (2025)
This article deals with the Investment Protection System in Peru, composed of Bilateral Investment Treaties —“BITs”—; Investment Chapters of Free Trade Agreements —“FTAs”—, as well as the State Coordination and Response System in International Investment Disputes —“SICRECI”—. This also includes the active participation of Peru as a State Party to the ICSID Convention, having a large number of arbitrations - concluded and pending - involving very diverse sectors, along with an evaluation of what could be the reasons that have generated this great variety of cases, under investment protection treaties, Concession Contracts, Legal Stability Agreements and License Contracts for the Exploitation of Hydrocarbons.